GROWTH AND YIELD RESPONSE OF OKRA (Abelmoschus esculentus (L.) Moench) TO FERTILIZER TYPE AND TIME OF APPLICATION IN THE SOUTHERN GUINEA SAVANNA AGRO-ECOZONE OF NIGERIA - Fasakin, Kola (Journal of Agricultural Sciences (Belgrade), 2019)
Abstract: A field study was carried out at the Kwara State University Teaching and Research Farm, Malete, to evaluate the response of vegetative growth and immature fruit yield of okra (Abelmoschus esculentus (L.) Moench) to three fertilizer types and three times of application. The fertilizer types, used at the rate of 60 kgN/ha, were Kwasu organic-based fertilizer type 2 (KOBF-2), Aleshinloye organo-mineral fertilizer grade A (AOMF-A), and inorganic NPK 15-15-15 fertilizer (NPK), each applied at planting time, 2 weeks after planting (WAP), and 4 WAP. The trial was laid out in a 3 x 3 factorial structure in a randomized complete block design and replicated three times. All the data collected were subjected to analysis of variance, using SAS statistical package, and the treatment means, where significant, separated using Duncan’s Multiple Range Test at 5% probability level. The results indicated no significant differences in plant height, number of leaves/plant, number of fruits/plant, and average length of the fruits between fertilizer types and application times. However, there were significant differences in leaf area/plant at 6WAP and fruit yield. Irrespective of time of application, KOBF-2 gave significantly higher immature fruit yield (2,840.92 kg/ha) than NPK (1,926.63 kg/ha) and AOMF-A (1,722.44 kg/ha). The results thus suggest that the new organic-based fertilizer formulated in this study (KOBF) deserves incorporation into national fertilizer progammes for sustainable crop production.K